Imperatives - Jary, Mark 1964-; Kissine, Mikhail (Cambridge, United Kingdom Cambridge University Press, 2014)
"Imperative sentences usually occur in speech acts such as orders, requests, and pleas. However, they are also used to give advice, and to grant permission, and are sometimes found in advertisements, good wishes and conditional constructions. Yet, the relationship between the form of imperatives, and the wide range of speech acts in which they occur, remains unclear, as do the ways in which semantic theory should handle imperatives. This book is the first to look systematically at both the data and the theory. Part I discusses data from a large set of languages, including many outside the Indo-European family, and analyses in detail the range of uses to which imperatives are put, paying particular attention to controversial cases. This provides the empirical background for Part II, where the authors offer an accessible, comprehensive and in-depth discussion of the major theoretical accounts of imperative semantics and pragmatics"--Provided by publisher.
Machine generated contents note: Part I. The Data: 1. What is the imperative mood?; 2. Imperative mood and directive force; 3. Imperatives with conditional meanings; Part II. The Theories; Introduction to Part II: from data to theory; 4. The imperative is directive force; 5. Declarative-like semantics for imperatives; 6. The imperative as a distinct semantic type; An opinionated conclusion; Appendix A. Possible worlds and semantics; Appendix B. Modality in possible-word semantics; Appendix C. Stalnaker's common-ground model of assertion; Glossary.
Includes bibliographic references (pages 307-319) and index.
Keywords: Grammar, Comparative and general -- Imperative